2003
DOI: 10.1007/s00134-003-2003-9
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent high permeability hemofiltration in septic patients with acute renal failure

Abstract: High permeability hemofiltration is a new approach in the adjuvant therapy of sepsis that facilitates the elimination of cytokines. HP-HF alternating with conventional hemofiltration is well tolerated. Further studies are needed to analyze whether HP-HF is able to mitigate the course of sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 21 publications
3
61
0
3
Order By: Relevance
“…Others have studied membranes with higher cut off values (around 100 kDa). Their results show high SC and clearances, but albumin loss becomes significant (13,14,16,(21)(22)(23). With the membrane used in our study, albumin loss is timely and quantitatively limited (17,20).…”
Section: Resultsmentioning
confidence: 82%
“…Others have studied membranes with higher cut off values (around 100 kDa). Their results show high SC and clearances, but albumin loss becomes significant (13,14,16,(21)(22)(23). With the membrane used in our study, albumin loss is timely and quantitatively limited (17,20).…”
Section: Resultsmentioning
confidence: 82%
“…Albumin SC for HCO techniques was reported in one paper and found to be 0.026. 16 Among the cytokines studied, the SC for TNF-alpha using HCO techniques appear to be consistently very low.…”
Section: Resultsmentioning
confidence: 95%
“…47 Standard techniques include both hemofiltration using standard filters at standard doses 13,17,18,20,22,23,35,[39][40][41]43,49,51 as well as hemofiltration at high volume doses 19,49 according to current definitions; with the latter labeled as HVHF. Standard or high cut-off techniques included continuous hemofiltration, 13,[15][16][17][18]20,22,23,35,[39][40][41]43,49,51 continuous hemodialysis 15,18,27,45 and continuous hemodiafiltration. 21,[24][25][26]36 The main cytokines measured in the clinical studies were interleukin-1b (IL-1b), interleukin-6 (IL-6), interleukin-8 (IL-8), interleukin-10 (IL-10), tumor necrosis factor-alpha (TNF-alpha) and interleukin-1 receptor antagonist (IL-1Ra) Other cytokines measured were interleukin-2 (IL-2), interleukin-2 receptor (IL-2R), interleukin-6 receptor (IL-6R) and soluble TNF-alpha receptors I and II (sTNFaRI and sTNFaRII).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Albumin loss was comparable between HCO haemofiltration, HCO haemodialysis, and HCO haemodiafiltration. 66 Morgera et al 67 published the first study on the use of HCO haemofiltration among septic shock patients and showed good IL-6 (but not TNF-α) clearance. Subsequently, Morgera et al 68 conducted an RCT that involved 30 septic AKI patients who were randomised to HCO or conventional haemofiltration.…”
Section: High Cut-off Haemodialysis/ Haemofiltrationmentioning
confidence: 99%